2018
DOI: 10.1111/dom.13180
|View full text |Cite
|
Sign up to set email alerts
|

LH‐21 and abnormal cannabidiol improve β‐cell function in isolated human and mouse islets through GPR55‐dependent and ‐independent signalling

Abstract: This study showed that Abn-CBD and LH-21 improve human and mouse islet β-cell function and viability. Use of islets from GPR55 mice suggests that designation of Abn-CBD and LH-21 as a GPR55 agonist and a CB1 antagonist, should be revised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 62 publications
8
23
0
Order By: Relevance
“…Notwithstanding, immunohistological analysis of pancreas showed that treatment with Abn-CBD greatly lowered islet cell apoptosis while induced beta cell proliferation, thus promoting preservation of beta cell mass. These findings are in agreement with our previous work showing a proliferative and protective role of Abn-CBD against cytokine-induced apoptosis on isolated islets from lean mice and human (21). Similar observations were also obtained in STZ-induced diabetic mice by another group (15).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Notwithstanding, immunohistological analysis of pancreas showed that treatment with Abn-CBD greatly lowered islet cell apoptosis while induced beta cell proliferation, thus promoting preservation of beta cell mass. These findings are in agreement with our previous work showing a proliferative and protective role of Abn-CBD against cytokine-induced apoptosis on isolated islets from lean mice and human (21). Similar observations were also obtained in STZ-induced diabetic mice by another group (15).…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, Abn-CBD was found to improve glucose tolerance in streptozotocin-induced diabetic mice (15). In agreement with these findings we recently reported that Abn-CBD decreases cytokine-induced apoptosis in mouse and human isolated islets while promoting beta cell proliferation (21). However, the impact of Abn-CBD on obesity-related metainflammation and its relationship with prediabetes and NAFLD remains unstudied.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Table S3. Images were visualized using a Nikon A1 Inverted Confocal microscope and analysed blindly before quantification using Fiji Image J software (https ://fiji.sc) [4]. For each experiment, the images were acquired with the same settings and histological quantifications were performed in paraffin sections that had been immunostained under the same conditions.…”
Section: Islet β-Cell Proliferationmentioning
confidence: 99%
“…agonists like lysophosphatidylcholine (LPC) and abnormal Cannabidiol (abn-CBD) did not show any significant modulation in the cyclic AMP (Ruz-Maldonado et al, 2018, Drzazga, 2018; however, CB2 agonists have been shown to inhibit cyclic AMP (Herring et al, 1998). Additionally, literature shows, GPR55 heterodimerizes with CB2 to modulate downstream cell signaling (Balenga et al, 2014), further, GPR55 ligands also promote receptor coupling to multiple cell signaling pathways (Henstridge et al, 2010).…”
Section: Discussionmentioning
confidence: 99%